2018
DOI: 10.1088/1674-1056/27/11/117202
|View full text |Cite
|
Sign up to set email alerts
|

Twin boundary dominated electric field distribution in CdZnTe detectors

Abstract: The performance of CdZnTe X/γ-ray detectors is strongly affected by the electric field distribution in terms of charge transport and charge collection. Factors which determine the electric field distribution are not only electric contact, but also intrinsic defects, especially grown-in twin boundaries. Here, the electric field distribution around twin boundaries is investigated in a CdZnTe bicrystal detector with a {111}-{111} twin plane using the Pockels electro-optic effect. The results of laser beam induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In the past, various bicrystals containing different types of grain boundaries out of copper [1,15,16], brass [17], nickel-base superalloy [18], and ferrosilicon alloy [19] were successfully grown using this method, which usually involves the seeded growth of single crystals with pre-selected orientations. Nowadays, the vertical Bridgman technique is widely used to grow semiconducting crystals due to the excellent electrical properties of single-and bicrystals [20][21][22]. In addition, the vertical Bridgman method was recently successfully used in deformation and microstructure studies on magnesium to investigate the mesoscopic interaction between dislocations and twin boundaries [8,23], as well as the accommodation of lattice rotations in the vicinity of the GB [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, various bicrystals containing different types of grain boundaries out of copper [1,15,16], brass [17], nickel-base superalloy [18], and ferrosilicon alloy [19] were successfully grown using this method, which usually involves the seeded growth of single crystals with pre-selected orientations. Nowadays, the vertical Bridgman technique is widely used to grow semiconducting crystals due to the excellent electrical properties of single-and bicrystals [20][21][22]. In addition, the vertical Bridgman method was recently successfully used in deformation and microstructure studies on magnesium to investigate the mesoscopic interaction between dislocations and twin boundaries [8,23], as well as the accommodation of lattice rotations in the vicinity of the GB [10].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al indicate an uneven electric field on both sides of the grain boundary within the CdZnTe detector [3] . Dong et al found that the distorted electric field was the reason for the sudden increase of laser-induced transient photocurrent signal [4] . It should point out that the extended defects may be different from homogeneous crystal in the chemical composition and crystallographic structure, result in different electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Time-of-flight technique (TOF) has been widely used to obtain the information about carrier transport properties and distribution of electric field inside a crystal. [14][15][16] Alpha source, x-ray machine, and γ -ray source, which are commonly used in the TOF measurements, usually have the disadvantage of random uncertainty. Therefore, in this study, a pulsed laser is used as an excitation source; this laser has good monochromaticity and can be easily controlled to systematically study the effect of space-charge perturbation on carrier transport process in CdZnTe semiconductor.…”
Section: Introductionmentioning
confidence: 99%